Exploring Mechanical Behavior in Pinewood/Polyethylene Composites Under Influence of Moisture, UV Radiation and Coupling Agent - Javier Guillen-Mallette; Irma Flores-Ceron; Soledad Cecilia Pech-Cohuo; Edgar Jose Lopez-Naranjo; Carlos Vidal Cupul-Manzano; Alex Valadez-Gonzalez; Ricardo Herbe Cruz-Estrada (Research Advances in Environment, Geography and Earth Science Vol. 6, 2024)
The present study aims to comprehensively analyze the effects of moisture absorption-desorption (AD) cycles, the amount of coupling agent, and UV radiation (UV) on the absorbed-desorption moisture and the flexural and tensile properties of WPC made from pinewood waste and high-density polyethylene (HDPE). Wood-plastic composites (WPC) incorporate lignocellulosic fillers into plastics to generate advantages in terms of stiffness, mechanical strength, cost-effectiveness and reduced weight. They use lignocellulosic waste to reduce the consumption of natural resources and promote better sustainable practices. First, the effect of UV radiation and the presence of anhydride-grafted polyethylene on the moisture absorption-desorption behavior of the compounds was evaluated, and then its effect on the mechanical properties. Scanning electron microscopy (SEM) was used to analyze the surfaces of the samples subjected to these factors and their subsequent damage in the fracture zones of the samples. A two-stage mechanism was observed in the water absorption-desorption process. The first stage is characterized by notable increases in absorption values over the first five cycles, while the second stage of stabilization starts from the sixth cycle. Initial absorption and delamination, capillary action and polymer-wood interaction, swelling, fiber-matrix interaction, and mechanical damage are all included in the first stage. The second stage involves the balance and stabilization step. Statistically, it was found that the changes in humidity values in the absorption and desorption cycles show that UV radiation has a significant contribution with the effect of increasing the absorption and desorption values, while the presence of polyethylene grafted with anhydride has a minor effect with an effect of decreasing those values. UV rays and moisture cycling had a major impact on the composite’s tensile and flexural performances. Tensile and flexural characteristics showed only a modest increase of 5–12% when compared to the sample without anhydride–grafted polyethylene and without treatments; however, treatments with UV radiation and moisture absorption–desorption cycles reduced them by up to 45%. The SEM analysis confirmed the deterioration of the composites in the form of microcracks, delaminations, interfacial voids and mechanical failures in both the wood filler and the polyethylene matrix, especially in the samples exposed to ultraviolet radiation, where this deterioration was lower in the samples containing anhydride-grafted polyethylene. The mechanical properties of the composites are influenced by the interactions between the wood filler and the polymer matrix, where UV radiation and humidity cycles produce damage in the interfacial zone. UV radiation primarily contributes to the damage, while moisture absorption-desorption cycles play a secondary role.